Cardiovascular risk in patients with psoriasis-relationship with oxidative stress and dyslipidemia - Karanikolic, Vesna; Bakic, Mirjana; Gluscevic, Sanja; Mercantepe, Filiz; Klisic, Aleksandra (Journal of Medical Biochemistry, 2025)
Background: Patients with psoriasis are at an increased risk of cardiovascular disease (CVD). Psoriasis and atherosclerosis share the common soil of inflammation and oxidative stress in their pathogenesis. The current study aimed to examine cardiovascular risk in relation to some non-traditional (i.e., biomarkers of oxidative stress and inflammation) and traditional metabolic parameters in patients with psoriasis. Methods: A total of 68 (57% men) patients with psoriasis were included. Traditional metabolic parameters, markers of oxidative stress [i.e., oxidation protein products (AOPP), malondialdehyde (MDA), catalase (CAT), and superoxide dismutase (SOD)] and inflammation (C-reactive protein) were measured. The atherosclerotic cardiovascular disease (ASCVD) risk score was used to measure CVD risk. Patients were divided into ASCVD score tertiles. Results: Patients with a higher ASCVD score had significantly lower high-density lipoprotein cholesterol (HDL-C), higher triglycerides (TG), and higher TG/HDL-C ratio (p for trend p<0.001). Among redox status parameters, only AOPP showed significant increase in parallel with the ASCVD score increase (p=0.011). In univariate binary logistic regression analysis, AOPP [OR, 95% CI=1.027 (1.004-1.051), p=0.021] and TG [OR, 95% CI =7.220 (2.041-25.548), p=0.002] correlated with the ASCVD risk score. In multivariate analysis (backward method) only TG was an independent predictor of ASCVD score [OR, 95%CI =7.220 (2.041-25.548), p=0.002]. Conclusion: The results show the association between ASCVD score and oxidative stress (AOPP) and dyslipidemia (TG), respectively, in patients with psoriasis, but only TG retained its independent association with ASCVD risk score. The measurement of serum TG levels is of great importance in patients with increased ASCVD risk concerning psoriasis.